Water Use Efficiency of Salt Tolerant and Non-Tolerant Wheat Varieties under Irrigated Saline Regimes - Kumar, P.; Sarangi, A; SINGH, D K; Parihar, S. S. (Journal of Agricultural Engineering, 2014)
Enhancing productivity from irrigated saline environment is of paramount importance to meet the increasing food demand in India. An experiment was conducted during rabi seasons of 2009-10 and 2010-11 with different irrigation water salinity levels and four wheat varieties, including 3 salt tolerant and one non-salt-tolerant.The yield of nonsalt tolerant variety HD-2894 irrigated with ground water (EC 1.7 dS.m-1) was highest (5.25 t.ha-1) with WUE of 18.62 kg.ha-1.mm-1. The salt tolerant variety KRL-1-4, however, produced highest yield of 4.6 t.ha-1, 4.2 t.ha-1 and 3.9 t.ha-1at irrigation water salinity levels of 4, 8 and 12 dS.m-1, respectively, during rabi 2010-11 with average yield higher by 26% and 41% as compared to non-salt tolerant variety HD2894 at irrigation water salinity levels 8 and 12 dS.m-1, respectively.The average water use efficiency of KRL-1-4 under salinity levels of 4, 8 and12 dS.m-1was 12.51 and 15kg.ha-1.mm-1 as compared to 8.75 and 10.33 kg.ha-1.mm-1 for the non-salt tolerant variety during 200910 and 2010-11, respectively. Highest deposition of salt was at the top 15cm soil depth ranging from 1.21 t.ha-1in ground water irrigated plot to 6.22 t.ha-1 in plots with salinity level of 12 dS.m-1. About 66% of salt got deposited in the root zone depth up to 75cm during the crop growth period. It emerged that as the salinity of irrigation water increases, a switchover from high yielding non-salt-tolerant variety to a salt tolerant variety is desirable to achieve higher yields and higher water use efficiencies.